Stimulatory Effect of Tofacitinib on Bone Marrow Adipocytes Differentiation - Letarouilly, Jean-Guillaume; Paccou, Julien; Badr, Sammy; Chauveau, Christophe; Broux, Odile; Clabaut, Aline (Frontiers in Endocrinology, 2022)
Background Systemic inflammation is the main factor underlying secondary osteoporosis in patients with rheumatoid arthritis (RA). Janus kinase inhibitors (JAKi), such as tofacitinib (Tofa), can control systemic inflammation and may have beneficial effects on bone in various models. This might be due to direct effects on the bone microenvironment and not exclusively based on their anti-inflammatory function. Bone marrow adipocytes (BMAds) are abundant in the bone microenvironment. The effect of JAKi on BMAds is unknown, but evidence suggests that there is competition between human bone marrow-derived stromal cell (hBMSC) differentiation routes towards BMAds and osteoblasts (Ob) in osteoporosis. Objectives The aims of the study are to determine whether Tofa influences BMAds and Ob derived from hBMSCs and to investigate the potential effects of Tofa on bone marrow adiposity in RA patients. Methods To determine the effect of Tofa on cellular commitment, hBMSCs were differentiated to BMAds or OBs for 3 days together with Tofa at 200, 400, or 800 nM and TNFα. This study was also conducted using differentiated BMAds. The impact of Tofa was determined by gene and protein expression analysis and cell density monitoring. In parallel, in a pilot study of 9 RA patients treated with Tofa 5 mg twice a day (NCT04175886), the proton density fat fraction (PDFF) was measured using MRI at the lumbar spine at baseline and at 6 months. Results In non-inflammatory conditions, the gene expression of Runx2 and Dlx5 decreased in Ob treated with Tofa (p <0.05). The gene expression of PPARγ2, C/EBPα, and Perilipin 1 were increased compared to controls (p <0.05) in BMAds treated with Tofa. Under inflammatory conditions, Tofa did not change the expression profiles of Ob compared to TNFα controls. In contrast, Tofa limited the negative effect of TNFα on BMAd differentiation (p <0.05). An increase in the density of differentiated BMAds treated with Tofa under TNFα was noted (p <0.001). These findings were consolidated by an increase in PDFF at 6 months of treatment with Tofa in RA patients (46.3 ± 7.0% versus 53.2 ± 9.2% p <0.01). Conclusion Together, these results suggest a stimulatory effect of Tofa on BMAd commitment and differentiation, which does not support a positive effect of Tofa on bone.